Productivity and phenology of tahiti acid lime in a subtropical region of Paraná state - Villa, Fabíola; Faria, Felipe Bock; Klosowski, Elcio Silverio; Tsutsumi, Claudio Yuji (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The aim of the present study was to evaluate the productivity and phenological phases of the Tahiti acid lime, cultivated in a subtropical area in western Parana. Two experiments were conducted on private property, from April/2014 to March/2015. The plant material used were plants of four years old, variety IAC-5 grafted on rootstock Trifoliata Flying Dragon. The experiment I consisted of fruits collected weekly from 300 lemon plants in production, resulting in the total of collected fruits every month. The second experiment consisted of the phenological phase’s characterization, carried out by a range of notes and through photographs of the principal phases of plants development reproductive. The experimental design used in the experiments was randomized blocks containing three blocks, twelve plots and four replications per plot. The annual average productivity achieved in the assay is close to average the northwest of the state. The phenological stages of Tahiti acid lime culture occur continuously throughout the year; major changes may occur due to environmental conditions and market conditions that they are exposed. The climatic conditions of subtropical area, as air temperature and rainfall, influence the phenological stages of Tahiti acid lime.